Epidemiological Features and the Incidence of Injuries in Iran in 2016 - Hossein Akbari; Mehrdad Mahdian; Hamid Reza Gilasi; fatemeh sadat Asgarian (Journal of Biostatistics and Epidemiology, 2022)
Introduction: Accidents and related injuries are the major public health problem and they have long been charged with being very destructive and deadly to the humans in the world. Regarding the widespread damage caused by accidents in Iran